Analysis Of Investment Effectiveness In Uzbekistan - Khoshimov Sobir Murtazaevich; Ganiev Shahiriddin Vohidovich (Academia One Publishing, 2024)
The article examines the role and importance of investment in fixed assets in the development of the country's economy, analyzes the effectiveness of investments using the example of sources of financing investments and types of economic activities, and also discusses conclusions and recommendations based on international experience
Keywords: investment climate; gross domestic product; sources of investment financing